The foundations of the knowledge of muscle strength - Platonov, V. N. (EWF Scientific Magazine, 2020)
PRESENTING BEAUTIFUL, UNPUBLISHED WORK IN A DESERVING MANNER We are indebted to Prof. V.N. Platonov for the concession to let us publish his previously unpublished material, a part of which appears in this special issue of the magazine, dedicated to strength and training. We felt it was particularly useful and significant to present Platonov`s materials divided into concise paragraphs: approximately one for each concept. We also numbered the paragraphs so the reader will be able to grasp its conciseness and progression, its clarity and essential nature. 160 points, to express a fundamental part of the concepts: the true foundations of the knowledge of muscle strength, a title that we thought apt for this work.